Media Audio Barcode Monitoring Book (Dicotobook) Effectively Improves Detection of Stunting Risk - Mirabella Hasmanita, Maharani; Simbolon, Demsa; Linda, Linda (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Stunting is the growth retardation that occurs in children as a result of chronic malnutrition, recurrent infections, and persistent psychological and social stress. 88 toddlers in Bengkulu City experienced stunting with a prevalence of 0.86%. This study aims to determine the effectiveness of the Audio Barcode Monitoring Book (Dicotobook) media on maternal behavior in the early detection of stunting. Methods: This study used a quasi-experiment design with a pretest-posttest design with a control group. The sample in this study was breastfeeding mothers, totalling 30 people in the intervention group and 30 in the control group using a purposive sampling technique. Data analysis in this study used the Wilcoxon signed rank test, the Mann-Whitney test, and the Analysis of Covariance test. Results: The statistical test results showed differences in mothers' average knowledge, attitudes, and actions before and after education using Dicotobook media (intervention group) (p-value 0.001) and leaflet (control group) (p-value 0.001). Education with Dicotobook media is more effective in increasing knowledge (p-value 0.004), attitudes (p-value 0.009), and actions (p-value 0.016) in the early detection of stunting risk after controlling for factors such as maternal education, maternal occupation, and distance to health facilities. Conclusion: Dicotobook media is a very suitable educational media that can motivate improvement in knowledge, attitudes, and actions in the early detection of stunting risk. This Dicotobook media can be used as an alternative to provide education to the public.